Pollinators, mates and Allee effects: the importance of self‐pollination for fecundity in an invasive lily. (3rd April 2013) - Rodger, James G.; van Kleunen, Mark; Johnson, Steven D.
Summary: Ability to self‐fertilize is correlated with invasiveness in several introduced floras, and this has been attributed to its mitigating effect on fecundity when pollinator visitation and mate availability are inadequate. Cross‐pollination opportunities are expected to be most limited in isolated individuals and small populations, both typical of the leading edge of an invasion. Thus, self‐pollination may promote invasion in part by mitigating pollen‐limitation Allee effects. We used emasculation and pollen supplementation experiments to test whether the importance of self‐pollination for fecundity increased as plant abundance decreased and isolation increased, in the hawkmoth‐pollinated and autonomously self‐pollinating invasive lily Lilium formosanum, in its introduced range in KwaZulu‐Natal, South Africa. As inbreeding depression is negligible in these populations, seed production through selfing is likely to be demographically important. In naturalized populations of L. formosanum, varying in size and degree of isolation, emasculation reduced seed production by two‐thirds, indicating strong reliance on self‐fertilization for fecundity due to inadequate pollinator visitation. However, this was not related to population size and was only greater for more isolated populations in one of the 3 years in which the experiment was carried out. Pollen supplementation experiments showed that pollen limitation was low – 12% on average – and significant in only one of 3 years, demonstrating that autonomous self‐pollination was highly effective. In artificial arrays, consisting of plants placed inside naturalized populations or in pairs isolated (3–702 m) from populations, the effect of emasculation on fecundity was greater in isolated plants than those inside the population in one of two populations. Isolation reduced fecundity when emasculated plants were placed next to a second emasculated plant, but not when emasculated plants were partnered with an intact plant, from which they could receive pollen. We conclude that self‐fertilization in L. formosanum compensates for inadequate pollinator visitation across all levels of population size and for a pollen‐limitation Allee effect due to decreased mate availability in isolated plants, and may thus play an important role in invasion. Abstract : Lay Summary Abstract :